2020
DOI: 10.1039/c9tb02691f
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-/copper-substituted dicalcium silicate cement: advanced biomaterials with enhanced osteogenesis and long-term antibacterial properties

Abstract: Dicalcium silicate (C2S) cements doped with Zn or Cu exhibited appreciable osteogenic activity and prolonged antibacterial potential in comparison with C2S cement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Cu, Co, and Zn were studied here as recognized components of solid osteogenic materials [ 11 , 12 , 13 , 49 ]; however, therapeutic effects of these TMs in cryogel scaffolds toward soft tissues have not been compared to date. The composition of TM-containing cryogels was optimized so that the metal dopants did not show a cytotoxic effect, while they were able to stimulate the proliferative and functional activity of mammalian cells ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu, Co, and Zn were studied here as recognized components of solid osteogenic materials [ 11 , 12 , 13 , 49 ]; however, therapeutic effects of these TMs in cryogel scaffolds toward soft tissues have not been compared to date. The composition of TM-containing cryogels was optimized so that the metal dopants did not show a cytotoxic effect, while they were able to stimulate the proliferative and functional activity of mammalian cells ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Implanted Co-containing borosilicate glass-based scaffolds remarkably enhanced bone regeneration and the vascularized network of the calvarial defective site in rats [ 12 ]. Likewise, Zn incorporation into Ca-silicate-based cements increased the osteostimulative activity of the composite material in a maxillofacial bone defect model in rabbits [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ewald et al (2012) [ 34 ] observed an enhancement of the expression of bone-specific proteins in osteoblastic cells seeded on a scaffold loaded with Cu ions. Recently, Zhang et al (2020) [ 35 ] synthesized a Cu-substituted dicalcium silicate cement and showed that the quantitative new bone formation was significantly higher with Cu cement than for undoped cement. Thus, the use of materials doped with copper ions, able to both prevent infections and promote wound healing, represents a promising research subject.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Zn 2+ toxicity level reported in the literature seems to be very close to the maximum concentration of Zn 2+ in GPCA. Studies have indicated that the addition of low levels of Zn in biomaterials enhances cell proliferation and protein synthesis [27,79,80]. Brauer et al showed that the addition of Zn has a dose-dependent effect on the cytotoxicity of GPC, on which the addition of 300 µM of Zn increased mouse osteoblast metabolic activity, while the GPC exposed to 400 µM of Zn showed a reduction in cell metabolic activity [73].…”
Section: Discussionmentioning
confidence: 99%